Foto Prewedding di Kalangan Masyarakat Jayapura dalam Sudut Pandang Sosial Keagamaan - Faisal, Faisal; Hairani, Debby Riana; Zulihi, Zulihi (Institut Agama Islam Negeri Fattahul Muluk Papua, 2023)
The purpose of this research is to find out: The community practices pre-wedding photos and the factors that influence the practice of pre-wedding photos among Muslim communities in Regency and Jayapura City. This is a qualitative research, using the social phenomenology paradigm. Research results: People think that pre-wedding photos in invitations or displayed in front of the wedding building as identity the bride and groom. Pre-wedding photos used on invitation cards or as decoration for wedding party decorations. The pose of the bride and groom are dominant aspects of making pre-wedding photos which are symbols consisting of concepts. Imitation and modification in the practice of pre-wedding photos both through media which is sometimes without a filter from the community to counteract. Pre-wedding photos are due to trends that occur in modern society. The issue of photography becomes clear when mapped that the law can be mubah or permissible if it does not violate religious provisions. Conversely, it can become haram if the photo is against religious law. In Islamic perspective, making out before muhrim even though they have made an engagement is not justified. It is forbidden to take photos with men and women who are not muhrim, ikhtilat (mixing of men and women), khalwat (being alone together) and kasyfulaurat (opening the aurat). The work of prewedding photographers is forbidden because it is considered to show a willing attitude to sin.